1979
DOI: 10.1007/bf02533868
|View full text |Cite
|
Sign up to set email alerts
|

Linolenic acid deficiency

Abstract: Linolenic acid deficiency has not been demonstrated clearly in warm blooded animals, yet circumstantial evidence suggests that n-3 fatty acids may have functions in these animals. The fact that several species of fish definitely require dietary n-3 fatty acids indicates that n-3 fatty acids have important and specific functions in these animals and suggests that such functions may also be present in warm blooded animals. It is also true that n-3 fatty acid distribution in tissues of birds and mammals appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(35 citation statements)
references
References 99 publications
2
32
0
1
Order By: Relevance
“…This compensation required only a rather small increase in all the n-6 PUFA (+ 20 %1, but this increase was considerable if we look at 22 : 5 n-6 ( x 2 or 31. This confirms that 22 : 5 n-6 is a true index of n-3 PUFA deficiency (Galli et al, 1974 ;Tinoco et al, 1979 ;Bourre et al, 1984 ;Youyou et al, 19861. The increase in n-6 PUFA and decrease in n-3 PUFA resulted in an augmentation of the ratio n-6/n-3 which rose from about 3 in soya rats to about 13 in sunflower ones. According to Budowski and Crawford (1985), this values in soya rats would be normal but, as Galli et a/.…”
Section: Dietary A-linolenic Acid Deficiency and Liver Lipidssupporting
confidence: 58%
“…This compensation required only a rather small increase in all the n-6 PUFA (+ 20 %1, but this increase was considerable if we look at 22 : 5 n-6 ( x 2 or 31. This confirms that 22 : 5 n-6 is a true index of n-3 PUFA deficiency (Galli et al, 1974 ;Tinoco et al, 1979 ;Bourre et al, 1984 ;Youyou et al, 19861. The increase in n-6 PUFA and decrease in n-3 PUFA resulted in an augmentation of the ratio n-6/n-3 which rose from about 3 in soya rats to about 13 in sunflower ones. According to Budowski and Crawford (1985), this values in soya rats would be normal but, as Galli et a/.…”
Section: Dietary A-linolenic Acid Deficiency and Liver Lipidssupporting
confidence: 58%
“…When linseed oil, a rich source of LnA, was substituted for maize oil, the n-6:n-3 value in the erythrocyte phosphoglycerides was reduced and the pathological symptoms were reversed. Lamptey & Walker (1976) reported that when rats were fed on a diet supplying only LA, the young of the second generation showed impaired learning ability compared with rats also receiving LnA in the diet; growth and reproduction were normal, although there was substantial replacement of "-3 FA by n-6 FA in the phosphoglycerides, as also reported by Tinoco et al (1978). LnA also seems to be needed for normal electroretinographic response in rats (Wheeler et al 1975) and visual acuity in the rhesus monkey (Neuringer et al 1984).…”
mentioning
confidence: 58%
“…The essentiality of LA in many animal species has been abundantly documented (Holman, 1968), and normal growth and reproduction can be sustained by LA alone over several generations, both in rats (Tinoco et al 1978) and guinea-pigs (Leat & Northrop, 1981). LnA and derived "-3 FA have been shown to be essential for trout (Sinnhuber et al 1972).…”
mentioning
confidence: 99%
“…23 Recent studies, however, have raised the possibility that co-3 fatty acids may be essential, not for prostaglandin synthesis, but as vital structural components of specialized membranes. 24 For example, docosahexanoic acid (C22:6 co-3) appears to play a role in the proper functioning of nervous tissues, 25 and impaired maze-running abilities have been found in co-3 fatty-acid-deficient rats. 26 Remarkably high levels of C22:6 co-3 are found in brain and retinal cells as well as in spermatozoa.…”
Section: Polyunsaturated Fatty Acid Families and Interrelationshipsmentioning
confidence: 99%
“…26 Remarkably high levels of C22:6 co-3 are found in brain and retinal cells as well as in spermatozoa. 24 Although further studies will be required to document structural or metabolic defects resulting from dietary co-3 fatty acid deprivation, the presence of high levels of these unique acids in certain tissues and the known Inability of mammalian cells to synthesize these de novo imply a dietary requirement for co-3 fatty acids.…”
Section: Polyunsaturated Fatty Acid Families and Interrelationshipsmentioning
confidence: 99%